PERANAN INTERNAL CONTROL TERHADAP PENGENDALIAN KAS PADA PT. BANK MASPION INDONESIA, TBK - Agustina Agustina; Thomas Sumarsan Goh; Elidawati Elidawati (STIE-PMCI, 2018)
This study aims to determine the role of the internal control system to control cash at PT. Bank Maspion Indonesia, TBK. Data analysis technique used is the descriptive method that is by doing direct observation and interview with the object under investigation. While secondary data obtained from the literature review that is data that already exist in the form of written reference and internet search.Based on the results of this study can be concluded that the internal control system (internal control) applied by PT. Maspion Indonesia Bank, TBK is sufficient in the company's cash control although in some cases still need improvement. As for some things to do improvements in cash control at PT. Maspion Bank Indonesia, TBK, among others, in the expenditure of bank branch cash that require approval from the center to make the operational activities of the bank to be disturbed.Â Keywords : internal control system, internal control, cash control, cash